Formulasi Macaroni Schotel Berbasis Ayam, Jamur Tiram, dan Kelor sebagai Upaya Intervensi Gizi Spesifik pada Balita - Enggar Anggraeni; Theresia Puspita (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2026)
Supplementary feeding programs (PMT) using local food ingredients are one strategy for addressing nutritional issues. These PMT activities should be accompanied by nutrition and health education, support for exclusive breastfeeding, and hygiene and sanitation education for families. Utilizing moringa leaves, which are readily available to the community, can enhance the nutritional value and appearance of the chicken and oyster mushroom macaroni schotel formulation in the preparation of PMT for toddlers. PMT activities using locally sourced food are expected to promote sustainable food and nutritional self-reliance for families. This experimental study aims to analyze the potential impact of an intervention using formulations of chicken meat, oyster mushrooms, and moringa leaves as PMT for toddlers at the Flamboyan Mrican Posyandu within the service area of the Mrican Public Health Center in Kediri City. The results of the descriptive analysis showed that the highest mean score for the aroma attribute was found in treatment F1, at 3.8. The color attribute in treatment F3 scored 4,3, the taste attribute in F1 scored 4.3, and the texture attribute in F2 and F3 scored 4,6. The results of the Kruskal-Wallis test indicated that only color showed a significant difference. The taste, aroma, and texture aspects did not differ significantly among the three formulas. The best treatment level, as determined by the organoleptic test results as well as nutritional quality and energy value, was treatment 1 (F1) with a composition of chicken meat, oyster mushrooms, and moringa leaves (70:20:10). Meanwhile, the results of the acceptability test using the Comstock method, conducted on 18 toddlers at the Flamboyan Mrican Posyandu in Kediri City, showed an average food residue of 25% for the toddlers, which falls into scale 2.